The Amount of Water-Soluble Vitamins Was Determined by High-Performance Liquid Chromatography - Safarov, Jasur; Sultanova, Shakhnoza; Mirkomilov, Abdurakhmon (American Journal of Biology and Natural Sciences, 2025)
A high-performance liquid chromatography (HPLC) method was developed and validated for the simultaneous quantification of water-soluble vitamins (C, B₁, B₂, B₃, B₆, B₇, B₉, B₁₂) in food samples. Extraction was performed on 5-10 g of sample using 40 % ethanol: boiling with magnetic stirring for 1 h, standing at 20 °C for 2 h, two successive extractions with 25 mL each, combining filtrates and diluting to 100 mL, then centrifuging at 7000 rpm for 10 min. Working standards (1 mg/mL) were prepared by dissolving 50 mg of each vitamin in 40 % ethanol to 50 mL. The mobile phase comprised an acetate buffer-acetonitrile system, providing sharp separation and excellent reproducibility. This method is suitable for routine monitoring of water-soluble vitamin content in food and pharmaceutical matrices.